Construction of high density genetic map and quantitative trait locus mapping in a sorghum Tx623A × sudangrass S722 population. (4th December 2022) - Tu, Wenmiao; Wang, Lihua; Jin, Peng; Meng, Ruirui; Zheng, Jian; Liu, Yanlong; Wang, Yi‐Hong; Li, Jieqin
Abstract: Sorghum–sudanense is a hybrid of sorghum and Sudanese grass and is widely used in animal husbandry and aquaculture because of its high yield, excellent quality and wide adaptability. Using high‐throughput sequencing, we constructed a high‐density genetic map of sorghum Tx623A × sudangrass S722 with 103 recombinant inbred lines (RILs) in this study and mapped quantitative trait loci (QTLs) for plant height (PH), stem diameter (SD), tiller number (TN), fresh weight (FW) and dry weight per plant (DW). The map included 1610 markers with a total length of 2329 cM and QTL mapping identified 19 QTLs, including two for PH, three for SD, four for TN, four for FW and five for DW. We detected two QTL clusters containing overlapping QTLs for PH, FW and DW. Orthologs of three SD candidate genes from maize were found within two SD QTLs. The identification of these QTLs will be useful for cloning the corresponding genes for these traits and developing marker‐assisted selection (MAS) in future sorghum breeding programs.